1999
DOI: 10.1121/1.427135
|View full text |Cite
|
Sign up to set email alerts
|

Development of dispersion curves for two-layered cylinders using laser ultrasonics

Abstract: In this paper, laser-ultrasonic techniques are employed to develop a quantitative understanding of the underlying principles of the propagation of guided circumferential waves in two-layered cylindrical components. The high-fidelity, broad-bandwidth, point source/receiver and noncontact nature of these optical techniques are critical elements to the success of this work. The experimental procedure consists of measuring a series of transient, circumferentially propagating waves in a cylindrical waveguide and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…The 2-D fast Fourier transform (2D-FFT) has been used in many studies for successfully identifying guided wave modes from such multimode signals that have been simulated or measured by means of axial transmission method in free and multilayered plate and tube structures (Alleyne and Cawley 1991;Moser et al 1999;Heller et al 2000;Seifried et al 2002;Kley et al 1999;Koh et al 2002). In addition, Lefebvre et al (2002) reported use of the 2D-FFT for measurements in bone specimens.…”
Section: Introductionmentioning
confidence: 97%
“…The 2-D fast Fourier transform (2D-FFT) has been used in many studies for successfully identifying guided wave modes from such multimode signals that have been simulated or measured by means of axial transmission method in free and multilayered plate and tube structures (Alleyne and Cawley 1991;Moser et al 1999;Heller et al 2000;Seifried et al 2002;Kley et al 1999;Koh et al 2002). In addition, Lefebvre et al (2002) reported use of the 2D-FFT for measurements in bone specimens.…”
Section: Introductionmentioning
confidence: 97%
“…First of all, waves in cylinders are dispersive, that is, propagation speed of waves varies with frequency. This property has been investigated extensively, analytically [22], numerically [19,10] and experimentally [12,14,21], but still long-range monitoring is complicated.…”
mentioning
confidence: 99%
“…Cylindrical Rayleigh waves are always dispersive regardless if the cylindrical solid is layered or not, since the radius of curvature provides another characteristic length in addition to wavelength. Cylindrical surface waves have gained a lot of attention for its engineering applications in non-destructive evaluation of defects [10,11], residual stresses [12,13], and coating's material properties [14][15][16][17]. The dominating method for experimental measurement of cylindrical surface waves is laser ultrasound techniques [10] and a lot of analysis and applications have been reported before [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that surface waves can also propagate along a spherically [6][7][8][9] or cylindrically curved surface [10][11][12][13][14][15][16][17] of an elastic solid. In this paper, "cylindrical surface waves" will be referred to the surface waves propagating along the circumferential direction of a cylindrical solid.…”
Section: Introductionmentioning
confidence: 99%